The Influence of NCT 127 Brand Ambassador on The “Click” Toothpaste Brand Image in NCTzen - Kamila Alfiana Rahme; Serafine Angelina Yudianto; Eugenia Desta Riana Putri; Muhamad Nastain (APLIKATIF: Journal of Research Trends in Social Sciences and Humanities, 2022)
Toothpaste is one of the primary needs of the community, which means that the community needs its supply. As a dental health product, the type of toothpaste also has a significant influence, not only on dental health but also on fresh breath. Several companies with well-known toothpaste brands always try to promote their products in various ways. Through television and advertisements, like toothpaste "Click", whose sales are increasing due to cooperating with a K-pop music group from South Korea named NCT 127, a brand ambassador to support its sales and marketing. Therefore, this study aimed to determine whether and how much influence NCT 127 as brand ambassadors had on the brand image of the "Click" toothpaste product in the Nctzen fandom. The population in this study were followers of the Twitter account @nctzenbase, which has 752,000, while the research sample used the Slovin sampling technique with as many as 433 respondents. The instruments used in this study were brand ambassador and brand image questionnaires that researchers had modified. This type of research is quantitative research with a mixed-methods approach. The data obtained were then analyzed using SPSS software. The study results show that the brand ambassadors of NCT 127 influence the "Click" toothpaste brand image. The magnitude of the effect is 37,7% so that other factors as much as 63,3% are influenced by other variables not examined.